KAJIAN STRUKTURAL DAN NILAI PENDIDIKAN DALAM NOVEL GURU AINI KARYA ANDREA HIRATA - MOHAMAD ARI; NURHADI NURHADI; ESTI SWATIKA SARI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
This study aims to describe the Structure and Educational Values in the novel Guru Aini by Andrea Hirata. This research uses a qualitative descriptive research type. The subject of this research is the novel Guru Aini by Andrea Hirata in 2020. The results of the research show that (1) the intrinsic structure of the novel Guru Aini by Andrea Hirata in 2020 is: (a) the theme is the struggle of women in achieving their goals; (b) the characters and characterizations consist of the main characters, namely Desi and Aini, the characterizations of women who are strong and never give up until their wishes are achieved, and additional characters, namely Runding, the characterizations who are pessimistic, Ayah Desi, the characterizations are humorous, Ibu Desi, the character has a big heart, letting her daughter go to pursue her dreams. - Her goal, Aini's father is a child-loving character, Aini's character is responsible for supporting the family and Laila is a loyal friend; (c) The plot is forward plot: (d) The setting consists of the setting, namely the library, village house, lecture hall, class, official residence, and Aini's house; the time setting consists of morning, afternoon and evening; (e) third person's point of view as an observer. This novel tells about the lives of two figures who fight for education. the struggle of a Mathematics Teacher, namely Teacher Desi. This Desi teacher insisted on becoming a math teacher, her goal was very noble, namely to educate this nation from long ignorance. The journey of a Desi Teacher is not easy to become a Desi Teacher who is seen as a Great and eccentric teacher. This research is focused on knowing the educational values contained in the Novel Guru Aini by Andrea Hirata. The results of this study are that the educational values contained in the Novel Guru Aini by Andrea Hirata include the values of religious education, the values of moral education, the values of social education, and the values of cultural education. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan Struktur dan Nilai-nilai Pendidikan dalam novel Guru Aini karya Andrea Hirata. Penelitian ini mengunakan jenis penelitian deskriptif kualitatif. Subjek penelitian ini adalah novel Guru Aini karya Andrea Hirata tahun 2020. Hasil penelitian menunjukan sebagi(1) struktur intrinsik novel Guru Aini karya Andrea Hirata tahun 2020 yaitu: (a) tema yaitu Perjuangan wanita dalam meengapai cita - cita; (b) tokoh dan penokohan terdiri dari tokoh utama yaitu Desi dan Aini penokohannya wanita yang tegar dan pantang menyerah sampai tercapainya keinginannya, dan tokoh tambahan yaitu Runding penokohannya yang pesimis, Ayah Desi penokohannya yang humoris, Ibu Desi penokohannya berjiwa besar melepaskan putrinya pergi mengejar cita- citanya, Ayah Aini penokohannya penyayang anak, Ibu Aini penokohannya bertanggung jawab menghidupi keluarga dan Laila penokohannya setia kawan; (c) Alurnya yaitu alur maju: (d) Latar terdiri dari latar tempat yaitu perpustakaan, rumah desi, tempat kuliah, kelas, rumah dinas, dan rumah Aini; latar waktu terdiri dari pagi, siang sore dan malam hari; (e) sudut pandang persona tiga sebagai pengamat. Novel ini menceritakan tentang kehidupan Kedua tokoh yang memperjuangkan pendidikan. perjuangan seorang Guru Matematika, yaitu Guru Desi. Guru Desi ini bersikeras ingin menjadi guru matematika, tujuannya sangat mulia yaitu ingin mencerdaskan bangsa ini dari kebodohan yang panjang. Perjalanan Guru Desi tidaklah mudah untuk menjadi Guru Desi yang dipandang sebagai guru Hebat dan eksentrik. Penelitian ini difokuskan untuk mengetahui nilai-nilai pendidikan yang terkandung dalam Novel Guru Aini Karya Andrea Hirata. Hasil dari penelitian ini yaitu bahwa nilai-nilai pendidikan yang terkandung dalam Novel Guru Aini karya Andrea Hirata seperti nilai pendidikan religius, nilai pendidikan moral, nilai pendidikan sosial, dan nilai pendidikan budaya.